2016
DOI: 10.1080/09168451.2016.1184558
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human bitter taste receptors by polymethoxylated flavonoids

Abstract: Tangeretin and nobiletin are polymethoxylated flavonoids in citrus peel. Both tangeretin and nobiletin are bitter; however, their bitterness has not been evaluated using human bitter taste receptors (hTAS2Rs). We screened 25 kinds of hTAS2Rs and found that hTAS2R14 and hTAS2R46 received both compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The above data suggest that flavones modify sinonasal epithelial inflammation-induced up-regulation of Muc5AC, iNOS, and cytokines. As mentioned above, apigenin and chrysin may also activate T2R14 and T2R39 (61), whereas tangeritin may activate T2R14 and T2R46 but not T2R39 (99). We hypothesized that flavones may activate one or more of these T2Rs located in the upper respiratory epithelium (22,25).…”
Section: Flavones Activate T2r14 Expressed In Sinonasal Epithelial Cementioning
confidence: 87%
“…The above data suggest that flavones modify sinonasal epithelial inflammation-induced up-regulation of Muc5AC, iNOS, and cytokines. As mentioned above, apigenin and chrysin may also activate T2R14 and T2R39 (61), whereas tangeritin may activate T2R14 and T2R46 but not T2R39 (99). We hypothesized that flavones may activate one or more of these T2Rs located in the upper respiratory epithelium (22,25).…”
Section: Flavones Activate T2r14 Expressed In Sinonasal Epithelial Cementioning
confidence: 87%
“…In MFs encountering bitter bacterial agonists at sites of infection, activated T2Rs may "rev up" acute phagocytic activity while likely simultaneous toll-like receptor (TLR) stimulation up-regulates expression of iNOS and antimicrobial proteins such as lysozyme to further combat infection. Of note, T2Rs also respond to a variety of natural plant compounds associated with complementary medicines, including flavonoids [8,[47][48][49], as well as common clinical drugs [50,51]. Activation of extraoral T2Rs in MFs may underlie some effects of homeopathic plant-based treatments or off-target drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…3A-B; next page). Responses were blocked by pertussis toxin (PTX; Fig 3C), which ADP-ribosylates and inactivates Gαs that can couple to T2Rs (G i (47) and/or G gustducin (48)(49)(50) ). Responses to bacterial T2R14 agonist HHQ were blocked by T2R14 antagonist 4-fluoro-6methoxy-flavanone (15,51) (Fig.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…Prior studies of sinonasal immunity have demonstrated a T2R‐mediated mechanism for increases in CBF and other local immune defenses such as the release of NO and secretion of antimicrobial compounds . It is known that T2R activation by secreted bacterial products as well as other biologically active compounds results in NO production, which is not only directly bactericidal but also increases CBF. To determine whether the topical application of bacterial lysate may work by a similar mechanism of action, ALIs were pretreated with either a NOS inhibitor or inhibitors of bitter taste‐receptor signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has provided support for the role of taste receptors in the sinonasal epithelium to sense their environment and initiate local immune defenses including mucociliary clearance and antimicrobial product release . These taste receptors are known to be activated by secreted bacterial products, and other compounds with biological activity are continuously being discovered . Given this emerging role of the sinonasal epithelium in the regulation of upper airway immunity, the nasal delivery of topical agents that augment the natural host response is an attractive therapeutic option in the treatment of rhinosinusitis and other local disease.…”
mentioning
confidence: 99%